Growth Rate and Histamine Production of Klebsiella sp. CK02 Isolated from Skipjack Tuna Compared with Morganella morganii ATCC 25830 at Various Incubation Temperatures - Dityanawarman, Aldino; Dewi, Indun Puspita; Ratnawati, Susana Endah; Ekantari, Nurfitri; Tamplin, Mark (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2020)
One of an important quality parameter in tuna is the level of histamine content. The contamination of histamine in tuna is mainly due to the activity of histidine decarboxylase produced by the bacteria. A rapid growth of histamine producing bacteria is correlated with the practice of temperature abuse during handling. This study aimed to develop predictive growth modeling of two histamine-producing bacteria in the function of temperature. The growth and histamine production of Klebsiella sp. CK02 and Morganella morganii ATCC 25830 at various temperatures were measured in tryptic soy broth histidine (TSBH) and tuna fish infusion broth (TFIB) growth media. Broths were incubated at 4°C and 15°C for 7 days, and at 30°C and 40°C for 24 hours. The Baranyi and Roberts model was used with DMFit to determine primary growth kinectics, and the Ratkowsky square root model to describe bacterial growth rate as a function of temperature. Histamine production was enumerated by the apparent yield factor (pYhis/CFU) value. Growth rate increased with temperature, with a maximum rate at 40°C for Klebsiella sp. CK02 (0.740 log CFU/h) and M. morganii (0.578  log CFU/h). The Tmin for Klebsiella sp. CK02 in TFIB was -8.9°C, indicating better survival in low storage temperature, compare to M. morganii ATCC 25830. In addition, Klebsiella sp. CK02 produced a lower pYhis/CFU at 15 and 30°C compared to M. morganii ATCC 25830.